Amino acid appended perylene bisimides: self-assembly, immobilization on nanocrystalline TiO2, and electrochromic properties. (5th November 2018) - Lundy, Ross; Draper, Emily R.; Walsh, James J.
Abstract : Titanium dioxide (TiO2 ) nanoparticle films have been used as a conducting support for the immobilisation of alanine-appended perylene bisimides (PBI-A) via dip-coating and carboxylate chemisorption. Abstract : Titanium dioxide (TiO2 ) nanoparticle films have been used as a conducting support for the immobilisation of alanine-appended perylene bisimides (PBI-A) via dip-coating and carboxylate chemisorption. The solvent- and concentration-dependent supramolecular structures of aggregated PBI-A were successfully translated onto the TiO2 electrodes, providing a method to control PBI-A assembly on a surface suitable for multiple functionalities. Electron microscopy revealed the extent of aggregation on the surface, and how this affects electrochemical properties. The films showed electrochemical reversibility by cyclic voltammetry, and preliminary electrochromic studies show that three colour states could be accessed. Strategies to improve the overall device performance are discussed.